1992
DOI: 10.3109/00207459208986662
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a Proconvulsive Hormone in Humans

Abstract: The pineal gland and melatonin exert a major influence in the control of brain electrical activity and have been shown to be involved in seizure and sleep mechanisms. Since pinealectomy has been reported to result in seizures in experimental animals, it is assumed that melatonin has anticonvulsant properties. Indeed, limited studies in humans with temporal lobe epilepsy indicate that melatonin attenuates seizure activity. In the present communication we present evidence, based on magnetoencephalographic (MEG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…79 A few studies have reported a possible increase in seizure activity by melatonin. 80,81 However, in another review, Jain and Besag 82 analyzed 27 studies on the use of melatonin and found no significant overall increase in seizure activity in most studies, and those that did report an increase in seizure activity had patients with preexisting uncontrolled seizures.…”
Section: Pharmacologic Interventionsmentioning
confidence: 96%
“…79 A few studies have reported a possible increase in seizure activity by melatonin. 80,81 However, in another review, Jain and Besag 82 analyzed 27 studies on the use of melatonin and found no significant overall increase in seizure activity in most studies, and those that did report an increase in seizure activity had patients with preexisting uncontrolled seizures.…”
Section: Pharmacologic Interventionsmentioning
confidence: 96%
“…Experimentally, melatonin enhanced low Mg 2þ -induced epileptiform activity in the hippocampus, 85 whereas melatonin antagonists delayed the onset of pilocarpine-induced seizures. 86 Clinically, melatonin has been shown to induce electroencephalographic abnormalities in patients with temporal lobe epilepsy 87 and increase seizure activity in neurologically disabled children. 27…”
Section: Childhood Seizure Disordersmentioning
confidence: 99%
“…The results of the evaluation of MLT therapy in epilepsy have also been inconsistent. Initial case descriptions have suggested that melatonin may either reduce seizures [22] or exacerbate the course of epilepsy [23,24]. Recent larger studies of children with epilepsy have shown that exogenous melatonin decreased frequency and duration of seizures and improved quality of sleep in children and adults with intractable epilepsy [22,[25][26][27].…”
Section: Introductionmentioning
confidence: 98%